Root cortical anatomy is associated with differential pathogenic and symbiotic fungal colonization in maize - Galindo‐Castañeda, Tania; Brown, Kathleen M.; Kuldau, Gretchen A.; Roth, Gregory W.; Wenner, Nancy G.; Ray, Swayamjit; Schneider, Hannah; Lynch, Jonathan P. (Plant, cell and environment, 2019)
Root anatomical phenotypes vary among maize (Zea mays) cultivars and may have adaptive value by modifying the metabolic cost of soil exploration. However, the microbial trade‐offs of these phenotypes are unknown. We hypothesized that nodal roots of maize with contrasting cortical anatomy have different patterns of mutualistic and pathogenic fungal colonization. Arbuscular mycorrhizal colonization in the field and mesocosms, root rots in the field, and Fusarium verticillioides colonization in mesocosms were evaluated in maize genotypes with contrasting root cortical anatomy. Increased aerenchyma and decreased living cortical area were associated with decreased mycorrhizal colonization in mesocosm and field experiments with inbred genotypes. In contrast, mycorrhizal colonization of hybrids increased with larger aerenchyma lacunae; this increase coincided with larger root diameters of hybrid roots. F. verticillioides colonization was inversely correlated with living cortical area in mesocosm‐grown inbreds, and no relation was found between root rots and living cortical area or aerenchyma in field‐grown hybrids. Root rots were positively correlated with cortical cell file number and inversely correlated with cortical cell size. Mycorrhizae and root rots were inversely correlated in field‐grown hybrids. We conclude that root anatomy is associated with differential effects on pathogens and mycorrhizal colonization of nodal roots in maize. We hypothesized that root cortical anatomy influences root colonization by pathogenic and mutualistic fungi. Cortical aerenchyma, cell size, cell file number, and living cortical area were associated with colonization of maize nodal roots by Fusarium, root rots, and arbuscular mycorrhizal fungi in contrasting patterns. These results indicate that root anatomy affects colonization by pathogens and mycorrhiza differently, which opens the possibility of developing crops with root anatomical phenotypes that favour mutualistic relationships while suppressing pathogens.